Dynamic measurements of hydrogen reaction with La Ni(5-x) Sn(x) alloys - Borzone, Emiliano Manque (2013)
The study focuses on the reaction between hydrogen gas and LaNi5 xSnx alloys, where 0 x 0.5, in broad temperature and pressure ranges. It was performed by means of dynamic volumetric techniques using specific equipment developed at our laboratory. The substitution of Ni by Sn lowers the system equilibrium pressure and increases the hydrogen absorption reaction rate. Reaction pressures at room temperature range from 8 kPa (x ¼ 0.5) to 250 kPa (x ¼ 0). At 415 K the reaction pressure is within the range from 200 kPa to 4000 kPa for x ¼ 0.5 and 0, respectively. The measured characteristic absorption time at 750 kPa for LaNi5 is around 1 min, while it remains below 2.5 s for LaNi4.5Sn0.5. The maximum H concentration goes from 1.3 wt.% for LaNi5 down to 0.95 wt.% for LaNi4.5Sn0.5. These results are useful to identify a metal system where the hydrogen interaction equilibrium properties can be tuned in a wide pressure range by choosing the chemical composition and the process temperature.